Laser array spots thermography for detection of cracks in curved structures - Jinxinga, Qiu; Pei, Cuixiang; Yang, Yang; Liu, Haochen; Chen, Zhenmao (IOS, 2020)
The laser array spot thermography (LAST) is a fully non-contact and non-destructive method for the inspection of surface cracks with high efficiency. In this study, the detection capability of this method for the inspection of surface cracks in structures with curved surfaces is experimentally studied. The influence of the inspection angle on the crack imaging results is also investigated. The experiment results show that cracks in surface of the pipes with different dimeters can be detected and imaged by LAST.
Keywords: curved structures; inspection angle; surface crack; Laser array spot thermography